Smart City Policy Innovation in the City of Jambi - Makmun Wahid (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
This paper intends to describe the policy innovations of the Jambi’s government in realizing a smart city with a focus on the use of RT-based urban villages (Kampung Bantar) and its meaning for the welfare of urban residents. To explain this case, researcher used qualitative research methods. This method was used because this research is related to the local government's in-depth understanding of smart cities. This research requires secondary data in the form of official government documents, for example several regional regulations, mayoral decrees and regulations, as well as other documents regarding city development policies towards smart cities. Primary data is also used in the form of interview results with informants obtained through in-depth interviews. This paper will answer common questions: how is smart city in Jambi city implemented? Specifically, it will answer: what is the role of the village in realizing a smart city and giving meaning to the welfare of urban residents. The findings show that there is a strong relationship between leadership innovation and social capital in the utilization of settlements to realize Jambi as a smart city